SELF-ASSESSMENT SYSTEM AND CORPORATE TAXPAYER COMPLIANCE (CASE STUDY AT ONE OF THE TAX OFFICE IN BANDUNG CITY) - Maulana Yusup; Iwan Sidharta; Robbi Saepul Rahman; Siti Mia Lasmaya (Jurnal Computech & Bisnis (e-Journal), 2020)
Previous research results indicate that there are different behaviors towards taxpayer compliance in various countries that are burdened by the prevailing culture. This research verifies the effect of the self-assessment system on corporate taxpayer compliance. Respondents who participated in this study were 34 respondents. The data analysis test used simple regression analysis with the results showing that there was a significant effect of implementing the self-assessment system on taxpayer compliance with the business. The implication of the research result recommends that excellent service efforts are provided by providing counseling and socialization regarding the procedures for implementing tax administration so that it makes it easier for taxpayers to settle their tax obligations. Keywords: Taxation System, Self-Assessment System, Taxpayer Compliance.